CORRELATION BETWEEN CARDIAC ARRHYTHMIA AND THE LEVEL OF HYPOXEMIA ON THE SEVERITY OF CHRONIC OBSTRUCTIVE PULMONARY DISEASE - Muborak Salaeva S., Mavjuda Tagaeva H., Abdisalim Kulkaraev K., Minavar Tursunova U., Madina Saidmurodova S. (Journal Park Publishing, 2023)
Assessment of the level of PaO2 in patients with COPD (chronic obstructive pulmonary disease) makes it possible to diagnose manifestations of chronic respiratory failure (CRF), depending on the severity. The results of the clinical study noted that in COPD patients with worsening of the course of the disease, the degree of cardiorespiratory disorders increases, which is characterized by rhythm disturbances (76.6%) and hypertrophy of the right heart (23.4%) and the presence of P-pulmonale (55.3% ), and with the severity of hypoxemic manifestations.
Keywords: chronic obstructive pulmonary disease, cardiac arrhythmia, hypoxemia.